Analisis Kemampuan Literasi Numerasi Siswa Dalam Menyelesaikan Soal Cerita Pada Materi Operasi Bentuk Aljabar Di Kelas VII SMP Negeri 1 Siantar - Wilda Charistasya Vitauli Simamora; Yanty Maria Marbun; Gayus Simarmata (International Forum of Researchers and Lecturers, 2023)
This article explains the numeracy literacy abilities of junior high school students in solving word problems in algebraic operations material. This research was conducted at SMP Negeri 1 Siantar with a total of 32 students. Data was obtained through numeracy literacy skills tests and interview results, then the data was analyzed using descriptive study quality. The research results show that the ability of students with the highest scores can fulfill two to three indicators, while students with low numeracy literacy skills test scores only fulfill one indicator test. Failure to fulfill indicators is caused by student errors, including: 1) Not writing down the data information that is known and being asked, 2) Making mistakes in solving problems, 3) Making mistakes in calculating, and 4) Not writing conclusions on the questions obtained from the answers.